(untitled) (Journal of EAHIL, 2023)
GIDIF-RBM (Italian Association of Health Librarians) in collaboration with TDNet Group performed a trial to test different discovery tools (DTs) functionalities. DTs represent the effect of that long digital revolution which, has upset the library universe as it was known up to that moment. Aim of the trial was to test two search queries: “cystic fibrosis”, “osteoarthritis AND “chondrocyte” AND “cell therapy” using PubMed, Google Scholar, Ebsco EDS, Ex Libris Summon, and TDNet Discover tools. The working group examined the first twenty-five results for each query to determine the quality of the results in each tool, using PubMed as a benchmark. The search analysis included an evaluation of quality of the journals ranking via Shimago SJR, the number of citations for each paper, the years of publication, and how many of the first 25 results were open access. Research findings indicate that DTs are powerful tools when managed consistently and holistically under team supervision. To make the best use of them, students and teachers must have information literacy skills, such as the ability to identify, evaluate, organize, use, and communicate information.